2012
DOI: 10.1007/s10461-012-0280-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Risk Behavior and Type of Sexual Partners in Transnational Indigenous Migrant Workers

Abstract: Indigenous migrant workers (IMWs) have a high vulnerability to HIV and STDs due to poverty and marginalization. This study examined factors associated with sexual risk behavior (SRB) according to type of partner in transnational young male IMWs at a sugar cane agro-industrial complex in western Mexico. A total of 192 sexually active IMWs were recruited from four laborer shelters to participate in a sexual partner survey. The IMWs were interviewed about their sexual partners and practices over the last 12 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Self-employment was associated with an increased likelihood of having sexual intercourses with casual partners/sex workers. Perhaps individuals who are self-employed have a wider social network, which can facilitate more casual sexual events [ 33 ]. In addition, the current findings revealed that people with higher ages had a higher likelihood of having multiple sex partners, and of not using condoms with casual partners/sex workers.…”
Section: Discussionmentioning
confidence: 99%
“…Self-employment was associated with an increased likelihood of having sexual intercourses with casual partners/sex workers. Perhaps individuals who are self-employed have a wider social network, which can facilitate more casual sexual events [ 33 ]. In addition, the current findings revealed that people with higher ages had a higher likelihood of having multiple sex partners, and of not using condoms with casual partners/sex workers.…”
Section: Discussionmentioning
confidence: 99%
“…After arrival, they struggle with substandard employment conditions and access to adequate housing and healthcare services (Fernandez 2019;Norris et al 2012). Research on the social determinants of health (Krieger et al 2010) postulates that communities that experience prolonged exposure to adverse conditions, and limited access to health resources, are more likely to have an increased predisposition to behavioral health problems, such as psychological distress, SUDs, and other social impairments (Caballero-Hoyos et al 2013;Castro et al 2007). Therefore it is essential to trace the risks and protective factors moderating their health in order to develop targeted interventions.…”
Section: Ima-us: Within Group Differencesmentioning
confidence: 99%
“…In our study, those working white-collar jobs were less likely to have multiple sex partners in the last 12 months, compared to those who were unemployed. Unemployment can be considered as a risk factor for multiple partners due to a deprived social background and excess free time, which in turn can induce more frequent casual sexual events [36,37].…”
Section: Discussionmentioning
confidence: 99%